The Conception of Consumer Perceived Risk towards Online Purchases of Apparel and an Idiosyncratic Scrutiny of Perceived Social Risk: A Review of Literature - Maziriri, Eugine Tafadzwa; Chuchu, Tinashe (International Review of Management and Marketing, 2017)
A review of literature can be an explanatory, critical, and useful synthesis of a specific topic. The aim of this paper is to provide an overview of existing knowledge on the concept of perceived risk as well as perceived social risk. It is widely known in the related literature that consumer’s perceived social risks act as a chief barrier to online purchases of apparel products. However, it is imperative to note that very little attention has been kept to this precise concept leaving an academic gap. This research aims to contribute towards closing the research issue as such, by gathering data through existing literature. The study was qualitative in nature where conceptual analysis was accomplished through literature review of concepts such as risk, perceived risk, and perceived social risk. Having discussed the conception of perceived risk, perceived social risk was found to be an aspect that influences a consumers’ purchase decision of a product or store choice. Key findings of the study highlighted that retailers of apparels could overcome the challenge of consumer resistance due to perceived social risk through providing them with relevant useful information. Furthermore, providing consumers with sufficient information regarding products as well as the use of known brands enhances the consumer’s decision making process potentially leading to purchases. Keywords: Perceived risk, perceived social risk, consumers, online, apparel JEL Classifications: M3, M30, M31